Complete Genome of the Xanthomonas euvesicatoria Specific Bacteriophage KΦ1, Its Survival and Potential in Control of Pepper Bacterial Spot - Gašić, Katarina; Kuzmanović, Nemanja; Ivanović, Milan; Prokić, Anđelka; Šević, Milan; Obradović, Aleksa (Frontiers in Microbiology, 2018)
Xanthomonas euvesicatoria phage KΦ1, a member of Myoviridae family, was isolated from the rhizosphere of pepper plants showing symptoms of bacterial spot. The phage strain expressed lytic activity to all X. euvesicatoria strains tested and did not lyse other Xanthomonas spp., nor other less related bacterial species. The genome of KΦ1 is double-stranded DNA of 46.077 bp including 66 ORFs and an average GC content of 62.9%, representing the first complete genome sequence published for a phage infecting xanthomonads associated with pepper or tomato. The highest genome similarity was observed between phage KΦ1 and the Xanthomonas oryzae pv. oryzae specific phage OP2. On the other hand, when compared with other members of the genus Bcep78virus, the genome similarity was lower. Forty-four (67%) predicted KΦ1 proteins shared homology with Xanthomonas phage OP2, while 20 genes (30%) were unique to KΦ1. Phage KΦ1, which is chloroform resistant and stable in different media and in the pH range 5‒11, showed a high titer storage ability for at least two years at +4°C. Copper-hydroxide and copper-oxychloride reduced phage activity proportionally to the used concentrations and the exposure time. UV light was detrimental to the phage strain, but skim milk plus sucrose formulation extended its survival in vitro. The phages survived for at least seven days on the surface of pepper leaves in the greenhouse, showing the ability to persist on the plant tissue without the presence of the host bacterium. Results of three repeated experiments showed that foliar applications of the unformulated KΦ1 phage suspension effectively controlled pepper bacterial spot compared to the standard treatment and the untreated control. The integration of the phage KΦ1 and copper-hydroxide treatments resulted in an increased efficacy compared to the copper-hydroxide alone.